Reply to comment on' Pb1-x Cax TiO3 solid solution (x=0.0, 0.25, 0.50, and 0.75): A theoretical and experimental approach' - Longo, E. [UNESP]; Paris, E. C. [UNESP]; Pizani, P. S.; De Lázaro, S. R.; De Lucena, P. R.; Varela, J. A. [UNESP] (American Physical Society (APS), 2010)
Chandra [Phys. Rev. B 77, 017101 (2008)] disagrees with the coexistence of a pseudocubic structure with a long-range tendency for cubic symmetry and tetragonal in a short-range order for the Pb1-x Cax TiO3 (PCT) system obtained by the polymeric precursor method (PPM), as proposed in our original paper. However, we did not show the Rietveld results for the samples in this paper. The Rietveld refinement results shown clearly the coexistence of the tetragonal-cubic phases for the PCT synthesized by PPM instead of the tetragonal-orthorhombic structures as suggested by Chandra. © 2010 The American Physical Society.